Finite Element Analysis Using MATLAB of Oxidation Properties in H2O Vapor of Steel-T22 Alloy Coated by Simultaneous Y-Doped Chromizing-Siliconizing Process - Hussein, Sabah Kh.; Husssein, Abbas Kh.; Resin, Kadhim K. (Nahrain University College of Engineering Journal, 2008)
The application of a pack cementation of Y-doped chromium and silicon coatings on low alloy steel type-T22 yields a significant improvement in the oxidationresistance. Steel-T22 was coated with Ydopedchromizing-siliconizing. Diffusion coating was carried out at 1050 oC for 6 h under an Ar atmosphere by simultaneous Y-dopded chromizing-siliconizing process. Cyclic oxidation tests were conducted on the coated steel-T22 alloy in the temperature range 300-500 oC in H2O for 100 h at 5 h cycle. . The oxidation kinetics for coated system in H2O was found to be parabolic .Oxide phases that formed on coated system are SiO2 and Cr2O3. Finite element results show that there is a good agreement between FEM and experiments results.